(untitled) (BIRDEM Medical Journal, 2017)
Background: Mental illness stigma continues to be a major barrier for individuals with mental illness. Methods: This study was a descriptive cross-sectional study conducted among the mentally ill patients attending Out Patient Department (OPD) in a tertiary care hospital of Dhaka city of Bangladesh, during the period from May 2013 to November 2013. The objective of the study was to assess the family support and stigma among the respondents. A total of 151 patients of 18 to 60 years attending in the OPD, National Institute of Mental Health (NIMH), Dhaka were selected purposefully to conduct the study. An informed consent was taken from the patients or care givers. Information about socio-demographic and psychosocial data was collected using the questionnaire designed by the researcher based on Factors Influencing Neuroleptic Medication Taking Scale (FNIMTS). Diagnoses of mental illness were done according to Diagnostic and Statistical Manual of Mental Disorders Text Revision (DSM-IV-TR) by psychiatrists. Results: The commonest diagnoses among the respondents were the schizophrenias (56.3%), bipolar mood disorders (23.8%) and substance related disorder (6.6%). Most were insightful into their mental illness (89.4%). Most of the respondents rated their perception of family support as good (66.2%). Most of the respondents believed that they would be treated differently if people knew they had a mental illness (57.6%) or on drugs for mental illness (54.3%). Among the presently employed respondents (21.85%) most (57.75%) were uncomfortable with the idea of telling employer about mental illness or being on drugs for it. Conclusion: A bridge for communication between people with mental illness, their families, and health care practitioners, may be a useful framework for guiding efforts to reduce stigma. Community-based participatory research principles and lived experiences are crucial elements in stigma reduction endeavors. Birdem Med J 2017; 7(2): 148-154